Analisis Fonologi pada Dialek Sehari-hari Masyarakat Desa Adat Penglipuran Bali - Hendratno, Adityawan; Rizky, Alya; Kezia, Yohana; Fikri, Moh; Kirana, Citra Dewi; Sholihatin, Endang (Jurnal Ilmiah Wahana Pendidikan, 2025)
The article entitled "Analysis of Phonology in the Everyday Dialect of the Indigenous Village of Panglipuran Bali" aims to 1. know the phonological elements of the language of the Indigenous Panglipuran Bali 2. know the phonological impact on the diversity and variation of the dialect of the daily language of the Indigenous Penglipuran Bali. This research uses descriptive qualitative method/approach, data collected through direct observation and interviews with specially selected informants. Conclusion 1. the phonological elements of the language of the indigenous people of Panglipuran Village Bali is the dialectical and phonological processes that occur in the category of the sounding process. The element of phonology of the language of the Penglipuran indigenous village community in the form of "sounding process" is found in the vocal element. Their language is characterized by several words that end with the sound - the sound of the vowel letter "o" resulting from the absence of airflow resistance in the oral cavity. There is in the pronunciation of an expression such as "ki kijo" which means "where to go" "mo" means "want" so that this becomes a phonological sounding process that characterizes the Penglipuran village community.2.phonological impact on the diversity and variation of dialects of the daily language of the indigenous people of Panglipuran Village Bali is in the process of communication with fellow citizens, this dialect becomes a distinctive language that is used every day by the people of panglipuran village by having a characteristic sounding process that is in accordance with the use of words in the village of panglipuran.